Kajian Transport Kontaminan Konservatif dan Non Konservatif di Air Tanah Dangkal dengan Model Analitik - Dewi, Retno Syahriawati (Politeknik Negeri Madura, 2023)
Solid waste that is not managed properly can be a threat to the environment, such as groundwater contamination caused by leachate. Leachate is the liquid released from landfill due to biological degradation and infiltration rainfall. This research purpose to determine the contaminant transport of chloride (conservative) and COD (non-conservative) contaminants from leachate and to predict groundwater quality for a period used the development of Domenico's analytical model. The samples used for this research were samples of leachate, groundwater, and soil taken around the TPA Kopiluhur, Cirebon City. The leachate quality for the chloride parameter was 52.8 mg/L and the COD parameter was 3200 mg/L. The results of two-dimensional Domenico's analytical model explained that the spread of chloride contaminants reached ± 350 meter in the transverse direction and ± 2500 meter in the longitudinal direction, while the COD contaminants reached ± 150 meter in the transverse direction and ± 150 meter in the longitudinal direction. Prediction of groundwater quality for a period time used one-dimensional of Domenico's analytical model. The result of one-dimensional simulation explained that contaminants concentration will be increases with increasing landfill age. When landfill age reaches 50 years and 80 years, chloride concentrations in five wells of resident are still on the threshold of quality standard while COD concentrations in SAT 1 and SAT 2 exceed the quality standard based on PP No 22 of 2021 for Class 1.